Understanding decisions to use e‐cigarettes or behavioural support to quit tobacco: a qualitative study of current and ex‐smokers and stop smoking service staff. (11th December 2019) - Hartwell, Greg; Egan, Matt; Petticrew, Mark
Abstract: Aim: To examine factors influencing current and ex‐smokers' decisions to use e‐cigarettes or behavioural support, including potential impacts of any differences in perspectives between smokers and their local stop smoking services (SSSs). Design: Semi‐structured qualitative interviews followed by framework analysis, with the 'capability', 'opportunity', 'motivation' and 'behaviour' (COM‐B) model of behaviour change used to frame findings. Setting: SSSs and surrounding local areas in England. Participants: Interviewees ( n  = 46) were current or recent smokers ( n  = 29) and SSS staff or stakeholders ( n  = 17). Measurements: Interview topic guides explored influences on smokers' choice of quit method and characteristics of support offered by local SSSs. Findings: Current and ex‐smokers showed a range of views on potential risks from long‐term vaping, which appeared to be particularly relevant for the capability dimension of COM‐B. These different attitudes to vaping appeared to be linked to variations in people's perceived capability to assess evidence around e‐cigarettes' safety. Motivations for using or avoiding e‐cigarettes and SSSs often appeared to overlap: attitudes to both e‐cigarettes and nicotine replacement therapy from SSSs often reflected personal experiences and views on whether switching from smoking to these alternatives represented successful quitting or simply ongoing nicotine addiction. For smokers, opportunities to use e‐cigarettes or SSSs appeared to be largely determined by perceived time requirements. Furthermore, interviews with SSS professionals suggested that opportunities to access SSSs for ex‐smokers who were now regular vapers may be being influenced by different e‐cigarette policies adopted in individual areas. Conclusions: In England, smokers' decisions to use e‐cigarettes and local stop smoking services appear to be determined by varied influences across the COM‐B framework. Both smokers and stop smoking service professionals display diverse views about potential risks from e‐cigarettes, which has relevance for the provision of behavioural support as well as the uptake of vaping.